THE THEORY AND PRACTICE OF HIGHER EDUCATIONAL INSTITUTIONS MANAGEMENT IN UKRAINE - Kirdan, Olena; Pryshchepa, Svitlana; Savchenko, Nataliya; Tkachuk, Myroslava; Kirdan, Oleksandr (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The theory and practice of management of higher educational establishments of Ukraine has a long history and is characterized by considerable experience and traditions. The article presents the findings study of the theory and practice of management in higher educational institutions in Ukraine in XIX – beginning of XXI century. The main periods of development of the theory and practice of management in higher educational institutions in Ukraine in XIX – beginning of XXI century is determined: 1802–1832, 1833–1862, 1863–1883, 1884–1917, 1917–1920, 1921-1990, 1991–2019 years as well as the characteristic features and tendencies of each of them. Views of N. Pirogov (the complete autonomy, the decentralization of universities’ management, the Ministerial panel of respected scientists interuniversity publicity etc.), K. Ushinskiy (the internal university management, the management of schools district etc.), M. Kostomarov (the idea of «an open university», increasing the authority of the University and others) and others are actualized in the investigation. The works above authors as a reliable on the basis in the development of the new trend of interdisciplinary scientific knowledge – universitology.